Impact of the Classic Chinese Garden Soundscape With Focus on Physiological and Psychological Effects, Tested Through Eye-Tracking, and Subjective Evaluation - Sun, Minkai; Dong, Lu (Frontiers in Psychology, 2022)
Soundscape has been valued and practiced in classical Chinese garden designs. Some authentic patterns were even mentioned and used in gardening books hundreds of years ago. Though these patterns are well-known, how they work in a classic Chinese garden is still unclear. In this study, we chose one of the most famous soundscapes called Tingyuxuan (Listening to the Sound of Rain Hall) in Zhuozhengyuan (Humble Administrator’s Garden), Suzhou as the object. A video of the Tingyuxuan was captured on a rainy day, along with its sound. Twenty-four participants were asked to view this video twice (once with audio, once muted, in a random order). Eye-movement data and the subjective evaluation of participants were collected. The results showed that the participants’ visual attention is influenced by the sound of rain and helps them identify and observe the main element of the soundscape. Furthermore, participants experienced more positive feelings when viewing the video with the audio on.